(untitled) (The Voz a Vos Bulletin, 2025)
This pedagogical reflection is about the importance of performing arts schools in our current context, where theater stands as an art with transformative potential. It emphasizes that acting training must integrate theory and practice organically, connecting knowledge, doing, and being, where the actor’s trained body becomes an instrument of psychophysical expression. Through practical experimentation, confrontation with theory, and constant reflection, the performer develops a performing language, builds characters, and contributes to the political and transformative power of theater, learning primarily by "playing" in a collaborative and unique process.